A comparative study of low energy radiation responses of SiC, TiC and ZrC. (15th May 2016) - Jiang, M.; Xiao, H.Y.; Zhang, H.B.; Peng, S.M.; Xu, C.H.; Liu, Z.J.; Zu, X.T.
Abstract: In this study, an ab initio molecular dynamics method is employed to compare the responses of SiC, TiC and ZrC to low energy irradiation. It reveals that C displacements are dominant in the cascade events of the three carbides. The associated defects in SiC are mainly Frenkel pairs and antisite defects, whereas damage end states in TiC and ZrC generally consist of Frenkel pairs and very few antisite defects are created. It is proposed that the susceptibility to antisite formation in SiC contributes to its crystalline-to-amorphous transformation under irradiation that is observed experimentally. The stronger radiation tolerance of TiC and ZrC than SiC can be originated from their different electronic structures, i.e., the and bonds are a mixture of covalent, metallic, and ionic character, whereas the bond is mainly covalent. The presented results provide underlying mechanisms for defect generation in SiC, TiC and ZrC, and advance the fundamental understanding of the radiation resistances of carbide materials. Graphical abstract: